Efficacy of Endoscopic and Surgical Treatments for Gastroesophageal Reflux Disease: A Systematic Review and Network Meta-Analysis - Eun Jeong Gong (Journal of Personalized Medicine, 2022)
Although various endoscopic and surgical procedures are available for the treatment of gastroesophageal reflux disease (GERD), the comparative efficacy of these treatments has not been fully elucidated. This study aimed to comprehensively evaluate the efficacy of various endoscopic and surgical treatments for GERD. All relevant randomized controlled trials published through August 2021 that compared the efficacy of endoscopic and surgical GERD treatments, including radiofrequency energy delivery, endoscopic plication, reinforcement of the lower esophageal sphincter (LES), and surgical fundoplication, were searched. A network meta-analysis was performed to analyze treatment outcomes, including the requirement of proton pump inhibitor (PPI) continuation and GERD-health-related quality of life questionnaire score (GERD-HRQL). As such, 25 studies with 2854 patients were included in the analysis. Endoscopic plication, reinforcement of the LES, and surgical fundoplication were effective in reducing the requirement of PPI continuation compared to PPI therapy (pooled risk ratio (RR) (95% confidence interval [CI]): endoscopic plication, 0.34 (0.21–0.56); reinforcement of LES, 0.32 (0.16–0.63), and surgical fundoplication, 0.16 (0.06–0.42)). Radiofrequency energy delivery tended to reduce the requirement of PPI continuation compared to PPI therapy (RR (95% CI): 0.55 (0.25–1.18)). In terms of GERD-HRQL, all endoscopic and surgical treatments were superior to PPI therapy. In conclusion, all endoscopic or surgical treatments, except radiofrequency energy delivery, were effective for discontinuation of PPI medication, especially surgical fundoplication. Quality of life, measured by GERD-HRQL, also improved in patients who underwent endoscopic or surgical treatment compared to those who received PPI therapy.